Plasma Kallikrein-Kinin system mediates immune-mediated renal injury in trichloroethylene-sensitized mice. (3rd July 2016) - Wang, Hui; Zhang, Jia-xiang; Ye, Liang-ping; Li, Shu-long; Wang, Feng; Zha, Wan-sheng; Shen, Tong; Wu, Changhao; Zhu, Qi-xing
Abstract: Trichloroethylene (TCE) is a major environmental pollutant. An immunological response is a newly-recognized mechanism for TCE-induced kidney damage. However, the role of the plasma kallikrein-kinin system (KKS) in immune-mediated kidney injury has never been examined. This study aimed to explore the role of the key components of the KKS, i.e. plasma kallikrein (PK), bradykinin (BK) and its receptors B1R and B2R, in TCE-induced kidney injury. A mouse model of skin sensitization was used to explore the mechanism of injury with or without a PK inhibitor PKSI. Kidney function was evaluated by measuring blood urea nitrogen (BUN) and creatinine (Cr) in conjunction with histopathologic characterization. Plasma BK was determined by ELISA; Renal C5b-9 membrane attack complex was evaluated by immunohistochemistry. Expression of BK and PK in the kidney was detected by immunoﬂuorescence. mRNA and protein levels of B1R and B2R were assessed by real-time qPCR and Western blot. As expected, numerous inflammatory cell inﬁltration and tubular epithelial cell vacuolar degeneration were observed in TCE-sensitized mice. Moreover, serum BUN and Cr and plasma BK were increased. In addition, deposition of BK, PK and C5b-9 were observed and B1R and B2R mRNA and proteins levels were up-regulated. Pre-treatment with PKSI, a highly selective inhibitor of PK, alleviated TCE-induced renal damage. In addition, PKSI attenuated TCE-induced up-regulation of BK, PK and its receptors and C5b-9. These results provided the first evidence that activation of the KKS contributed to immune-mediated renal injury induced by TCE and also helped to identify the KKS as a potential therapeutic target for mitigating chemical sensitization-induced renal damage.